2009
DOI: 10.1111/j.1365-2044.2009.06031.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flexion on the level of termination of the dural sac in paediatric patients

Abstract: SummaryAlthough the anatomy of the spinal cord and its associated structures have been well defined, the effects of body position relevant to neuraxial blockade have not been elucidated. This study was designed to determine the effect of body position on the end of the dural sac in children. After induction of anaesthesia, ultrasound examination was performed to evaluate the location of the dural sac end in the lateral position with a straight back and knee, and in the lateral position with the knees, legs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Ultrasound can be easily used without radiation exposure and be an effective tool not only in locating the sacral hiatus but also in guiding needle insertion into the caudal space with reducing the risks of the intraosseous, intrathecal, or intravenous injection. 2,15,18,19 Despite these benefits, there are some considerations of using ultrasound for the caudal block such as the cost and extra time of using the high-quality ultrasound equipment or requirement of the sufficient education and experience of the physician. 20,21 In addition, so far there has been no report to prove that the guidance of ultrasound in caudal block is more advantageous than a conventional landmark-based method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound can be easily used without radiation exposure and be an effective tool not only in locating the sacral hiatus but also in guiding needle insertion into the caudal space with reducing the risks of the intraosseous, intrathecal, or intravenous injection. 2,15,18,19 Despite these benefits, there are some considerations of using ultrasound for the caudal block such as the cost and extra time of using the high-quality ultrasound equipment or requirement of the sufficient education and experience of the physician. 20,21 In addition, so far there has been no report to prove that the guidance of ultrasound in caudal block is more advantageous than a conventional landmark-based method.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The success of a caudal block is dependent on the proper insertion of a needle into the caudal epidural space with knowledge of the exact location of the sacral hiatus. 1 However, anatomical variations and obesity can make it difficult to identify the sacral hiatus.…”
mentioning
confidence: 99%
“…Although neither was significant, these results suggest that pain is managed equally as well with ultrasound-guided blocks, if not better than the traditional gold standard landmark technique, in patients undergoing circumcision. 36 Koo et al, 33,34 Shin et al, 28 Tachibana et al, 29 Ueda et al 39…”
Section: B (Us Vs Landmark Method)mentioning
confidence: 99%
“…33 In another observational study, ultrasound allowed for visualization of the sacral hiatus, which offers benefits relative to the equiangular triangle landmark technique, because the position of the sacral hiatus can vary based on patient age, weight, and height. 36 One study used ultrasound imaging to examine spinal structures and determine the prevalence of spinal dysraphism in children with urogenital anomalies.…”
Section: Neuraxial Anesthesiamentioning
confidence: 99%
“…Koo et al. (3) demonstrated that in this position dural sac shifts significantly cephalad providing some safety margin to avoid dural puncture.…”
Section: Discussionmentioning
confidence: 99%